Poor fruit set due to lack of pollinators in Aristolochia manshuriensis (Aristolochiaceae) - Olga Nakonechnaya; Olga Koren; Vasilii Sidorenko; Sergey Shabalin; Tatyana Markova; Alexander Kalachev (Plant Ecology and Evolution, 2021)
Background and aims – Interactions of insects with trap flowers of Aristolochia manshuriensis, a relic woody liana with fragmented natural populations from south-eastern Russia, were studied. Pollination experiments were conducted to identify the causes of the poor fruit set in this plant.Material and methods – The study was carried out at two ex situ sites within the natural range of A. manshuriensis in the suburban zone of the city of Vladivostok (Russia). The floral morphology was examined to verify how it may affect the process of pollination in this species. To test for a probability of self-pollination, randomly selected flowers at the female phase of anthesis (day 1 of limb opening) were hand-pollinated with pollen from the same plant. The daily insect visitation was studied. The pollen limitation coefficient and the number of visitors to the flowers were determined. To identify insects that lay eggs on the flowers, the insects were reared from eggs collected from fallen flowers. Both caught and reared insects were identified.Key results – The floral morphology and the colour pattern of A. manshuriensis are adapted to temporarily trap insects of a certain size. The hand-pollination experiment showed that flowers of this plant are capable of self-pollination by geitonogamy and require a pollinator for successful pollination. The positive value (2.64) for the pollen limitation coefficient indicates a higher fruit set after hand-pollination compared to the control without pollination. The number of visitors to the flowers was low (0.17 visitors per flower per day). Insects from three orders were observed on the flowers: Diptera (up to 90.9%), Coleoptera (8.3%), and Hymenoptera (0.8%). Four species of flies (Scaptomyza pallida, Drosophila transversa (Drosophilidae), Botanophila fugax, and Botanophila sp. 1 (Anthomyiidae)) are capable of transferring up to 2500–4000 pollen grains on their bodies and can be considered as pollinators of A. manshuriensis. Data of the rearing experiment indicate that flies of the families Drosophilidae (S. pallida, D. transversa), Chloropidae (Elachiptera tuberculifera, E. sibirica, and Conioscinella divitis), and Anthomyiidae (B. fugax, B. sp. 1) use A. manshuriensis flowers to lay eggs. Beetles were also collected from the flowers, but they were probably not involved in pollination, because no pollen grains were observed on them during our study.Conclusions – Pollinators of A. manshuriensis include mainly Diptera that lay eggs on the flowers. The poor fruit set (2%) in A. manshuriensis is associated with pollen limitation due to the lack of pollinators, as the number of visitors to flowers was extremely low. This may be due to the fact that the flowers of this species are highly specialized on insects of a certain size for pollination.